Novel approaches to predictive developmental and reproductive toxicology - Verslype, A (2023)
Toxicity assessments are important for evaluating the potential harm caused by chemicals such as pesticides, which are released into the environment. However, assessing the developmental and reproductive toxicity (DART) of these chemicals is a complex process that requires a thorough examination of the entire life cycle. The traditional method for DART testing involves using animal models such as rats and rabbits, but this approach has drawbacks. It is time-consuming, expensive, requires large amounts of test substances, and involves a significant number of animals. Moreover, the reliability of these tests in predicting the toxicity outcomes in humans remains uncertain.